Buffer-Induced Time-Dependent OFF-State Leakage in AlGaN/GaN High Electron Mobility Transistors on Silicon - Ming Tao; Wang, Maojun; Liu, Shaofei; Xie, Bing; Min Yu; Wen, Cheng P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Shen, Bo (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2016)
Time-dependent OFF-state leakage behavior of AlGaN/GaN MISHEMTs on silicon substrate is investigated and a novel degradation mechanism is proposed in this paper. Under constant high voltage OFF-state stress, drain leakage current gradually increases with stress time and the behavior is gate bias and temperature-dependent. Consecutive OFF-state breakdown measurement with drain injection technique indicates that the negative shift of threshold voltage (V-th) is responsible for the increase of drain leakage current during stress measurement. It is proposed that the negative shift of V-th is mainly induced by the ionization of uncompensated donor like deep levels near the channel, which are most likely to be located in the 300-nm-thick unintentionally doped GaN layer above the carbon doped buffer layer.